Lanthanum Complex with Neridronic Acid: Synthesis and Properties - A. V. Galantsev; D. V. Drobot; P. V. Dorovatovsky; V. N. Khrustalev (Тонкие химические технологии)
Currently, various amino bisphosphonates are widely used in the treatment of many bone diseases. One of the most well-known complex compounds of neridronic acid (6-amino-1-hydroxyhexylidene-1,1- bisphosphonic acid) is sodium neridronate – a bisphosphonate, which is used to treat osteogenesis and Paget's disease. However, there is no data on compounds of neridronic acid with rare earth elements. A new complex of lanthanum with 6-amino-1-hydroxyhexylidene-1,1-bisphosphonic acid (I) was obtained and characterized by various physicochemical methods (chemical analysis, IR spectroscopy, solid-phase 31P NMR spectroscopy, optical microscopy, PCA, DTA). According to the research data the complex I has the composition {La[(H3N-(CH2)5-C(OH)(PO2(OH))2]2(H2O)2}[OH]·H2O and represents the coordination 1D-polymer due to two bridged phosphonic groups with lanthanum atoms in a tetragonal-antiprismatic environment. In a crystal, polymer chains form a 3D-frame porous structure by means of strong hydrogen bonds O─H ··· O and N─H ··· O with endless channels, available to include a variety of inorganic anions or small organic molecules. A study under the microscope showed that the sample is needle crystals (thin rods) of different lengths. The particle size distribution was obtained by laser diffraction, and the average particle size was determined: 50 µm in length and 2.5 µm in thickness.